Access to Information and Medicines Regulation in New Zealand - Hill, Amy (Victoria University of Wellington Law Review, 2014)
This article explores a significant issue in the regulatory regime for medicines in New Zealand and around the world: the deficit of information about medicines available to doctors, patients and independent researchers. In New Zealand, while some generic (off-patent) drugs are manufactured domestically, the major suppliers are large multinational companies. Similarly, clinical trials to establish a drug's effectiveness, safety and quality are predominantly undertaken overseas. Much of the information about safety, efficacy and quality of drugs is held and controlled by pharmaceutical companies and regulators. This article proposes ways in which public access to information about medicines can be improved.